Geological constraints of a structural model of sector collapse at Stromboli volcano, Italy. Issue 9 (20th September 2016) - Vezzoli, L.; Corazzato, C.
Abstract: This study is focused on the reconstruction of the structure and dynamics of the first lateral collapse that occurred at Stromboli during the Holocene, which represents the structure inherited by all the following collapses that formed the present Sciara del Fuoco depression. The first lateral collapse of Stromboli occurred at the end of the Vancori volcano activity, at about 13 ka ago. The Neostromboli lava cone grew within this collapse amphitheater. Based on a comprehensive geologic and structural analysis of both Vancori and Neostromboli products, we propose an innovative interpretation of the sliding surface. Once considered to be a homogeneous landslide along a deep‐seated sliding surface, we demonstrate that the Upper Vancori failure was accommodated by a more complex deformation regime comprising an upper (proximal) domain of tilted megablocks (toreva) and a lower (distal) domain of fragmental landslide transport and deposition. Key Points: An innovative model of the first Holocene sector collapse of Stromboli is proposed based on new geological and structural constraints Complex failure deformation regime included proximal (back‐tilted blocks) and distal (fragmental landslide transport and deposition) domains